Identifying Muslim youth travelers’ perspectives on the attributes of shariah compliant hotel - Hamdan, Muhammad Hariz Irfan; Md Sawari, Siti Salwa (Kulliyyah of Languages and Management, 2019)
Sharia Compliant Hotel is one of the new emerging concepts and innovative services in Islamic tourism specifically in hospitality industry. This concept focuses more on the Muslim travellers and countries in providing services needed by Muslims. However, the concept is still at the initial stage and thus, more research is required because most of the people are still confusing with the Sharia terms especially the hotel owners. This research aims to recognise the Muslim youth traveller’s perceptions towards Shariah Compliant Hotel attributes. The data was collected using questionnaires which were distributed to 269 undergraduate students from Kulliyyah of Languages and Management (KLM), International Islamic University Malaysia (IIUM) and it was analysed using SPSS software. The findings showed that most of the respondents agreed that facilities were the most important attribute in Sharia Compliant Hotel. From these findings, it is recommended for students to take appropriate actions to experience and understand more about the Shariah compliant hotels. Further research should be conducted in other areas and among students of different universities using random sampling procedure.